Assessing the Prevalance of Immunization Status, Complications and Outcomes in Children with MMR (MMR,mumps,Rubella ):A cross sectional study - khan, Sonia; Jabeen, Nadia; soomro, Jaweria; Lal , Shanker; Aakash, Aakash; Neelam, Neelam; Wajid, Yumna; Mohan, Simrat; Muhammad, Khan; lal, Bheru; Fatima, Misha (Journal of Neonatal Surgery, 2025)
Background: The MMR vaccine is a combination vaccine that protects against measles, mumps and rubella. Mumps is a viral disease caused by the mumps virus, belonging to the family Paramyxoviridae and is characterized by swelling of the parotid glands and can lead to complications such as orchitis and meningitis. Measles is another infectious viral exanthema, caused by Morbilivirus belonging to the family Paramyxoviridae. The MMR vaccine is a combination vaccine that protects against two highly contagious and potentially serious viral diseases. Objective: To assess the immunization Status, complications and outcome in Children with MMR. Methodology: This cross sectional study was conducted at Dow university hospital. The study duration was of 1 year from January 2024 to December 2024. A total of 200 patients of either sex from the ages of 3 months to 13 years who presented with measles, mumps, rubella or with its complications were included. Detailed history and physical examination was done and findings entered in a proforma that had been prepared after thorough research of literature. Immunization status of the patients was checked by examining the National Expanded Program on Immunization (EPI) card where available or parental enquiry if EPI card was not available. All the relevant investigations like complete blood count, serum electrolytes and X- ray chest were carried out besides history and clinical examination. Cerebrospinal fluid examination was done where needed. Results: A total of 200 patients were admitted during the study period with measles, mumps, rubella or its complications. Male were 170 (85.3%) of and females accounted for 30 (14.7%). The vaccination status of the patients revealed that 113 (56.76%) had received complete vaccination against MMR, while 47 (23.24%) were unvaccinated and 40 (20%) were partially vaccinated. The most common complication was pneumonia affecting 90 (45%) patients, followed by gastroenteritis in 42 (22%) ,bleeding problems 8 (4%) and rarely orchitis 4 (2%) in patients. Notably, 56 (28%) patients had no complications